Segmenting the infra-red images of the scene into road and non-road regions - Sint Sint Win. (2008)
The major goal of this dissertation is to present a segmentation algorithm for semi-structured roads. This algorithm is developed to segment the infra-red images of scene. Our objective is to identify the road/non-road regions for night driving autonomous navigation system.